Investigation of plasma behavior during noble gas injection in the end-cell of GAMMA 10/PDX by using the multi-fluid code 'LINDA'. (31st October 2017) - Islam, M S; Nakashima, Y; Hatayama, A
Abstract: The linear divertor analysis with fluid model (LINDA) code has been developed in order to simulate plasma behavior in the end-cell of linear fusion device GAMMA 10/PDX. This paper presents the basic structure and simulated results of the LINDA code. The atomic processes of hydrogen and impurities have been included in the present model in order to investigate energy loss processes and mechanism of plasma detachment. A comparison among Ar, Kr and Xe shows that Xe is the most effective gas on the reduction of electron and ion temperature. Xe injection leads to strong reduction in the temperature of electron and ion. The energy loss terms for both the electron and the ion are enhanced significantly during Xe injection. It is shown that the major energy loss channels for ion and electron are charge-exchange loss and radiative power loss of the radiator gas, respectively. These outcomes indicate that Xe injection in the plasma edge region is effective for reducing plasma energy and generating detached plasma in linear device GAMMA 10/PDX.